Università è con-di-visione - Francesca Galgano (Cultura delle differenze: Diritto, conoscenza, formazione, 2019)
During the celebrations for the foundation of the University of Naples "Federico II", the Committee for Equal Opportunities, Well-being at Work and Against Discrimination of this University has staged a photography contest addressed to Federico II's scholars, students and employees. This volume deals with the first edition of this contest, whose theme is "University is con-di-vision" and it collects all the pictures involved, the motivations of the award and the declarations of the members of the jury.